A new partial cranium of Metridiochoerus (Suidae, Mammalia) from Malapa, South Africa. (September 2018) - Lazagabaster, Ignacio A.; Brophy, Juliet; Sanisidro, Oscar; Pineda-Munoz, Silvia; Berger, Lee
Abstract: Suidae cranial material is very scarce in South Africa. Here we present a newly found partial cranium recovered from the site of Malapa, South Africa. The cranium is dorsoventrally crushed and does not preserve dentition. We reconstruct the cranium using three-dimensional techniques based on more complete material from Eastern Africa. We assign the specimen to the genus Metridiochoerus and the species Metridiochoerus cf. M. andrewsi. The partial cranium described here constitutes one of the few of its genus recovered so far in South Africa. Highlights: New partial suid cranium, UW-88-1300 from Malapa (South Africa) is described. Three-dimensional reconstruction of the partial cranium is presented. The cranium bears large male zygomatic knobs typical of some suid taxa. We identify UW-88-1300 as Metridiochoerus cf. M. andrewsi.